Nanofabrication of magnetic thin films for high-density data storage application - Sun, Changqing (2008)
This project investigates the effect of particle size reduction and catalytic nitridation on the ferromagnetic behavior of Fe based films aiming at high-density data storage applications. Incorporating the bond-band-barrier(BBB)correlation and the bond-order-length-strength(BOLS)correlation mechanisms into the king model has enabled us to predict the magnetic and thermal stability of nitride and ferromagnetic nanosolid, in general. The prediction was confirmed by Monte Carlo simulation and experimental study of ultra thin Ni, Fe and iron nitride films deposited using FCVA technique.